Magnetism in organic radical ion salts based on nitronyl nitroxide derivatives substituted with heterocyclic aromatic hydrocarbons - Sugano, T; Blundell, S; Hayes, W; Day, P (2003)
Radical cation and anion salts of the neutral organic radicals, 2-imidazolyl nitronyl nitroxide (2-IMNN) and 2-benzimidazolyl nitronyl nitroxide (2-BIMNN), have been prepared and their magnetic properties studied by SQUID magnetometry. The radical salts exhibit one-dimensional (1-d) antiferromagnetic (AFM) intermolecular interactions with the exchange coupling J/k between -0.8 and -6.3 K, which are significantly reduced from those observed in the two neutral radicals, while 2-IMNN shows an AFM interaction with J/k= -88 K within the molecular dimers and 2-BIMNN has quasi 1-d ferromagnetic (AFM) intermolecular interactions with J/k = +22 K (intrachain) and zJ'/k = +0.24 K (interchain). The magnetic properties of the nitronyl nitroxide and iminonitroxide derivatives having molecular structure related to 2-IMNN have also been investigated. In 2-benzimidazolyl iminonitroxide (2-BIMIN), the FM interaction observed in 2-BIMNN is replaced by strong 1-d AFM interaction with J/k = -11.7 K. (C) 2003 Elsevier Science Ltd. All rights reserved.